2019
DOI: 10.1155/2019/1201958
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Time-Dependent Wellbore Collapse in Hard Brittle Shale Formation under Underbalanced Drilling Condition

Abstract: In recent years, the lithologic traps in a mid-depth formation are the focus of oil or gas exploration and development for eastern oilfields in China. The Shahejie Formation develops thick hard brittle shale, and the wellbore instability problem is prominent due to obvious hydration effect for long immersion time during drilling. Through the analysis of laboratory tests and field test results of physical and chemical properties and microstructure and mechanical properties of hard brittle shale, the instability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is also recognized that the seepage effect of the shale formation causes shale hydration, which has a significant impact on shale strength, and results in the reduction of cohesion and internal friction angle [13][14][15]. Wall rock strength decreases after prolonged exposure to drilling fluid [16][17][18]. A hydration test was conducted on the shale formation of Longmaxi, and it was discovered that the rock sample expanded with water absorption, permeated along the bedding, and finally peeled off the block [19].…”
Section: Introductionmentioning
confidence: 99%
“…It is also recognized that the seepage effect of the shale formation causes shale hydration, which has a significant impact on shale strength, and results in the reduction of cohesion and internal friction angle [13][14][15]. Wall rock strength decreases after prolonged exposure to drilling fluid [16][17][18]. A hydration test was conducted on the shale formation of Longmaxi, and it was discovered that the rock sample expanded with water absorption, permeated along the bedding, and finally peeled off the block [19].…”
Section: Introductionmentioning
confidence: 99%
“…The Longmaxi formation belongs to the hard and brittle shale, where the water absorption and diffusion coefficient and drilling fluid activity have obvious influences on wellbore expansion and strong sensitivity. Then, the drilling fluid immersion causes instability [28]. For the shale of the Longmaxi formation, water absorption and expansion experiments were carried out [8], and the results showed that hydration effect permeated along the bedding surface, and shale samples were stripped and dropped.…”
Section: Introductionmentioning
confidence: 99%